2018
DOI: 10.1136/bjophthalmol-2017-311694
|View full text |Cite
|
Sign up to set email alerts
|

Three-year outcomes after high hyperopia correction using photorefractive keratectomy with a large ablation zone

Abstract: High hyperopia correction with PRK using an aberration-neutral profile and large ablation zone provides good efficacy, safety, predictability and visual outcomes. Relatively low change of corneal spherical aberrations and low increase of hyperopia in the first three postoperative years were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…In the study by Frings A et al (2016), the mean SE before the PRK decreased from +1.04±0.58 to -0.08±0.38 at the 6 months postop [ 19 ]. Kaluzny BJ et al (2018) revealed that the mean SE decreased from +4.61±0.67 with a range of 3.6–6.15 D to -0.002±0.43 D at the 12 months postop [ 13 ]. Many other studies confirmed the significant decrease of the mean SE after PRK [2, 7–10, 12, 14, 15, 17, 20], which is in line with data from this study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the study by Frings A et al (2016), the mean SE before the PRK decreased from +1.04±0.58 to -0.08±0.38 at the 6 months postop [ 19 ]. Kaluzny BJ et al (2018) revealed that the mean SE decreased from +4.61±0.67 with a range of 3.6–6.15 D to -0.002±0.43 D at the 12 months postop [ 13 ]. Many other studies confirmed the significant decrease of the mean SE after PRK [2, 7–10, 12, 14, 15, 17, 20], which is in line with data from this study.…”
Section: Discussionmentioning
confidence: 99%
“…According to Autrata R et al [ 18 ], after 2 years of follow-up, 86% of patients in the PRK group showed an emmetropia of ±1.00 D interval and 57% SE of ±0.5 D in their eyes. In the studies by Kaluzny BJ et al [ 13 ] and Yenugandula R et al [ 21 ] (after 3 years), 78% and 92% of the eyes were in the range of ±0.5 and ±0.1.00 D, respectively. Also, in a study by El-Agha MS et al [ 4 ], in the PRK group, after one year, 83.3% and 100% of the eyes had an SE of ±0.5 D and ±1.00 D, respectively, which was not in line with our results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations